Targeted delivery of anti-inflammatory drugs in lower parts of gastrointestinal tract: Conventional and novel approaches - Čalija Bojan; Milić Jela (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
The therapy of inflammatory bowel diseases can be improved by development of new effective and selective biological drugs and efficiency improvement of existing, traditional anti-inflammatory drugs via targeting sites of inflammation. Targeted drug delivery upon peroral administration results in improved therapeutic efficacy, reduction of systemic side effects, decreases risk of drug to drug interactions, and in case of prolonged-release systems improves compliance/adherence by reduced frequency of drug intake. This article describes two approaches for targeted delivery of anti-inflammatory drugs in lower parts of gastrointestinal tract: conventional, based on specific physiological conditions of different parts of gastrointestinal tract (pH, enzymatic activity of intestinal flora and transit time) and novel, based on micro- and nanoencapsulation (e.g. polymeric and lipid micro- and nanoparticles, liposomes), with focus on the anti-inflammatory drugs intended for targeted delivery in lower parts of gastrointestinal tract available on market of Republic of Serbia.